Norway's polar territories - Barr, Susan (Aschehoug, 1987)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Peter I. Øy; geografi; geologi; historie; polarområdene; polarpolitikk

Palaeoceanography of the subantarctic South Atlantic - Ciesielski, Paul; Kristoffersen, Yngve (Nature, 1987)
Keywords: Sørishavet; oseanografi

Amundsens sydpolferd 1910-12: vitenskapelige resultater sett i lys av nyere målinger - Dannevig, Petter (Været: populærvitenskapelig tidsskrift, 1987)
Keywords: Antarktis; ekspedisjoner; historie; meteorologi

Fra Monica Kristensens antarktisekspedisjon 1986-87 - Dannevig, Petter (Været: populærvitenskapelig tidsskrift11, 1987)
Keywords: Antarktis; ekspedisjoner

Biochemistry of the autolytic processes in Antarctic krill post mortem. Autoproteolysis - Ellingsen, Trond E.; Mohr, Viggo (Biochemical Journal, 1987)
1. Autoproteolysis post mortem was examined at 0 degree C by following the changes in the major classes of krill (Euphausia superba and Euphausia crystallorophias) proteins and by liberation of peptides and free amino acids, and was based on experiments conducted on board expedition vessels in the Antarctic. 2. Primarily salt-soluble proteins were broken down during the first week of incubation, whereas water-soluble and insoluble proteins were degraded to a much smaller extent. The enzymes responsible for the hydrolysis presumably originate primarily from the digestive apparatus of the krill. 3. In general, the individual amino acids were released at rates corresponding to their relative occurrence in the bulk protein of the krill. Alanine was liberated in larger amounts than would be expected from the composition of the krill protein, and was evidently formed also by reactions other than proteolysis. Glutamic acid, and certain amino acids which presumably occur with high frequency adjacent to glumatic acid residues in the krill protein, were liberated only to a limited extent, and accumulated in smaller peptides. 4. During proteolysis, arginine seemed to be converted to some degree into ornithine, and on prolonged incubation conversion of arginine and lysine into their corresponding decarboxylation products, agmatine and cadaverine, appeared to take place.
Keywords: Sørishavet; biokjemi; krill; marin biologi; plankton

Botany of Bouvetøya, South Atlantic Ocean. II. The terrestrial vegetation of Bouvetøya - Engelskjøn, Torstein (Polar Research, 1987)
Keywords: Bouvetøya; botanikk; forskning; planter

Breeding ecology of the Antarctic petrel Thalassoica Antarctica in Mühlig-Hofmannfjella, Dronning Maud Land - Fridtjof, Mehlum; Claus, Bech; Svein, Haftorn (Proceedings of the NIPR Symposium on Polar Biology, 1987)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Geochemistry of basalt lavas from Vestfjella and adjacent areas, Dronning Maud Land, Antarctica - Furnes, Harald; Vad, Erik; Austrheim, Håkon; Mitchell, John G.; Garmann, Leif B. (Lithos, 1987)
K-Ar ages, major- and trace-element compositions, and Sr-isotope data are presented for basalt lavas from Vestfjella, Dronning Maud Land, Antarctica. The new conventional K-Ar age data have yielded ages from 171 ± 2 to 695 ± 11 Ma, but the youngest (i.e. Middle Jurassic) ages are preferred. Mineralogical and chemical data show that the majority of the basalts are tholeiites. Petrographic mixing calculations, REE modelling, and the Sr isotope data suggest that they were derived by partial melting of garnet-free lherzolites with variable REE patterns, and subsequently modified by fractionation of olivine, Ca-rich pyroxene and plagioclase. Incompatible trace-element data from nearby Middle Jurassic basalt lavas (from Kirwanryggen and Heimefrontfjella) suggest a different source and REE modelling indicates generation from garnet lherzolites.
Keywords: Dronning Maud Land; NARE 1976/77; geokjemi; geologi; mineralogi; paleontologi; petrografi

Geology, geophysics, and hydrocarbon potential of Antarctica continental margin of Weddell Sea - Hinz, K.; Kristoffersen, Yngve (AAPG Bulletin, 1987)
A prominent escarpment, called the Explora-Andenes Escarpment, has been recognized between long. 40°W, lat. 72°40primeS and long. 10°W, lat. 69°20primeS. It separates the continental margin from the Weddell Sea basin. Our recent MCS data have revealed the presence of some remarkably symmetric structures beneath a thick pile of tectonically undisturbed sediments. For example, two extensive wedge-shaped basement units occur between 20°W and 40°W. These units are characterized by a pattern of divergent reflectors which surround an elongated depression in basement. The northern wedge terminates against the Explora-Andenes Escarpment between 25°W and 30°W. The southern wedge, known as the Explora Wedge, shows a northward-dipping reflection pattern. The seismic characteristics suggest that both wedges consist of volcanic rocks. The basement depression is interpreted as a failed rift basin. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of "dipping reflectors." The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of dipping reflectors. The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures.
Meeting abstract from: AAPG Annual Convention, Los Angeles, California, June 7-10, 1987
Keywords: Antarktis; Sørishavet; Weddellhavet; geofysikk; geologi

Rosshavets base på Stewart Island - Hoff, Stein (Norsk sjøfartsmuseum. Årsberetning, 1987)
Publisher: Museet Place: Oslo
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; historie; hvalfangere; hvalfangststasjoner; pelagisk

The South Pole expedition 1910-1912 - Huntford, Roland (The Amundsen photographs, 1987)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; forskning; fotografihistorie; historie; oppdagelsesreiser; polarområdene

Interrelationships between egg dimensions, pore numbers, incubation time, and adult body mass in Procellariiformes with special reference to the Antarctic petrel Thalassoica antarctica - Mehlum, Fridtjof; Rahn, Hermann; Bech, Claus; Haftorn, Svein (Polar Research, 1987)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Levels and interactions of heavy metals in sea birds from Svalbard and the Antarctic - Norheim, Gunnar (Environmental Pollution (Barking, Essex: 1987), 1987)
Samples of liver and kidney from 92 seabirds of ten species collected on Spitsbergen and in the Antarctic, were analysed for their content of copper, zinc, cadmium, lead, mercury and selenium. Significantly higher levels of copper and zinc were observed in birds from Spitsbergen than in those from the Antarctic, while the opposite was true for selenium. The highest cadmium levels were found in fulmar Fulmarus glacialis and macaroni penguin Eudyptes chrysolophus. A possibility of kidney damage due to cadmium exists. The highest mercury levels were recorded in brown skua Catharacta lonnbergi collected at Bouvetøya. Lead was not detected in any of the birds. Significant correlations were observed between levels of several of the metals studied, especially between cadminum and zinc and between mercury and selenium. However, for all birds, the highest correlation coefficients were observed when the molar concentrations of cadmium plus mercury, and selenium plus zinc, were used in the calculations. Thus several protective mechanisms may operate to diminish effects of heavy metal contaminants.
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; NARE 1978/79; forurensning; fugler; miljøgifter; ornitologi

Evolution of under water sides of ice shelves and icebergs - Orheim, Olav (Annals of Glaciology, 1987)
A systematic programme of side-scan sonar and plumb- line soundings was carried out in the Weddell Sea area in 1985 to measure the under-water sides of ice shelves and icebergs. From these observations the following model is suggested for the evolution of the ice front: (1) Initial stage: fracturing of the ice shelves takes place along smooth, curvi-linear segments with vertical faces. (2) Formative stage: the freshly formed vertical face is eroded both by wave and swell action around the water line, by small calvings from the undercut, overhanging subaerial face, and by submarine melting. The melting has a minimum at 50–100 m depth, and increases with depth to a rate of around 10 m a−1 at 200 m, This is about twice the rate of erosion at the water line. The variation in melting with depth results from a combination of summer melting by near-surface water, and year-round melting by water masses that are increasingly warmer than the pressure melting-point with depth. (3) Mature stage: this stage is reached after a few years of exposure. The backward erosion of the face leads to a shape with a prominent under-water “nose” with a maximum projection to more than 50 m at 50–100 m depth. The ramp above this slopes upwards to meet the vertical wall about 5 m below the water line. The ice below the nose is melted back beyond the above-water face. There is no net buoyancy and ice shelves at this mature stage are generally not up-warped at the front.
Publisher: Cambridge University Press
Keywords: Sørishavet; glasiologi

Icebergs in the Southern Ocean (abstract) - Orheim, Olav (Annals of Glaciology, 1987)
Relatively little data on the distribution of Antarctic icebergs were available prior to 1980. The published literature included size data of about 5000 icebergs, and position data of 12 000 icebergs. There were indications that the size data were biased in favour of larger icebergs. A programme of systematic iceberg observations was therefore initiated by Norsk Polarinstitutt in 198! through the SCAR Working Group on Glaciology. This programme is based on standard “blue” forms distributed to all ships going to Antarctica. The icebergs are recorded every 6 h and in Five length groups: 10–50, 50–200, 200–500, and 500–1000 m, and those over 1000 m are described individually. The amount of data has increased greatly from the start in 1981–82. The position of 70 000 icebergs, including 50 000 that had been size classified, were on file at Norsk Polarinstitutt by December 1985, and the data set is growing rapidly. Most ships travelling to and from Antarctica now participate in collection of the data. ( shows the locations of the icebergs sighted.) Fig. 1. Location of iceberg observations under the programme initiated in 1981. Main ship tracks are clearly reflected. The average observation represents 14 icebergs. The size distribution of the classified icebergs observed under this programme up to December 1985 is given in : Table I The “standard size” (length, width, and thickness) is based on our observations from three Antarctic expeditions which carried out dedicated iceberg studies. Many icebergs are of course not right-angled parallelepipedal in shape, but this is a good approximation for most of the larger icebergs. The data are based both on visual sightings and on radar observations. Duplicate observations from a ship moving at slow or zero speed are as far as possible eliminated, both during observation, and by critical appraisal before the data are filed. The data editing also includes evaluation of data quality, especially in connection with radar observations, and comparison of positions and dimensions of the large icebergs in order to reduce to a minimum repeated observations from different vessels of icebergs >1000 m. These account for most of the iceberg mass (see ). Consideration of iceberg-distribution patterns and the observed area of the Southern Ocean, and of duplicate observations, indicates more than 300 000 icebergs south of the Antarctic Convergence, with a total ice mass of about 1016 kg. Consideration of mean residence times indicates an annual iceberg production from the continent of 23–1015 kg, which is considerably higher than most other recent estimates. This also suggests that the Antarctic ice sheet is in balance. The data indicate large regional differences in iceberg sizes, the most noticeable being between the two sides of the Antarctic Peninsula, and between the Amery Ice Shelf/ Prydz Bay area and the remainder of East Antarctica. These differences are probably mainly related to different calving sites. About one-third of the observed icebergs are over the continental shelf of Antarctica. The total under-water area of these icebergs is two orders of magnitude less than the under-water area of the Antarctic ice shelves. The annual total iceberg melting and its effect on the water masses over the continental shelf has been calculated from ocean-water temperature variations at 200 m depth and estimated melt rates. This turns out to be an order of magnitude less than the annual effect of melting sea ice. The iceberg data considered here are probably under-represented with respect to the smallest sizes, and they do not include icebergs that have become <10 m. Inclusion of these ice bodies would increase the total melt.
Publisher: Cambridge University Press
Keywords: Sørishavet; glasiologi

Snow and Ice Studies By Thematic Mapper and Multispectral Scanner Landsat Images - Orheim, Olav; Lucchitta, Baerbel K (Annals of Glaciology, 1987)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; is; satellittbilder; snø

The Antarctic scene: legal and political facts - Trolle-Andreson, Rolph (The Antarctic treaty regime : law, environment and resources, 1987)
Keywords: Antarktis; Antarktistraktaten 1959; internasjonal rett; jus